Action bids in children with speech impairments. (31st August 2021) - Fasulo, Alessandra; Nomikou, Iris; Nye, Joanna
Abstract : The paper illustrates a practice, which we have called 'marking', observed in play interactions between parents and children with Down syndrome (DS) aged 3–8 years. Markings are minimal turns that rely on prosody, embodied resources and indexicality to foreground events within an ongoing activity and convey a stance toward them. Markings can be both retrospective and prospective (i.e. referring to a just-occurred or an incipient event). As first pair parts, they are open action bids that prompt recipients to display their co-orientation towards the referent. Responses from parents (i.e. second markings) can take the form of repeats or expansions; after prospective marking the recipient can also add support to the incipient activity the child has marked. We discuss marking as the core constituent of a larger family of actions for 'sharing noteworthiness', but also as a designedly undetermined action bid with specific conversational uses for children and adults alike.